The 102-foot Australian Invasion of Central Wellington in the 1920s - Mew, Geoff; Humphris, Adrian (Architectural History Aotearoa, 2011)
A significant change to the building bylaws by the Wellington City Council in the early 1920s allowed for the design and erection of much taller buildings in the central city than had previously been permitted. Coupled with the use of steel frames and concrete floors, buildings started to reach eight or nine storeys; not tall by American standards, but regarded as skyscrapers in a city where three- and four-storey buildings were still the norm. The fact that several of the most prominent of these new buildings were designed mainly by Australian architects, both in the 1920s and the early 1930s, does not seem to be widely known, or has been partially concealed by quoting the local supervising architects as the prime movers in the planning. Some of the buildings were erected to house branches or Wellington head offices of Australian firms but others were solely for New Zealand clients. The firm of A & K Henderson of Melbourne led the way with their 1926 design of the T & G Building (now Harcourts) on Lambton Quay, in association with Atkins and Mitchell. Australian born and trained Llewellyn Williams had already designed the tall, but narrow, Druids Chambers further to the north and went on to oversee more tall structures in the next few years. Hennessy & Hennessy, also Australian, pioneered Wellington Art Deco designs in the early 1930s. Both the building techniques and the architectural styles employed showed strong American influences, particularly the tripartite form developed in Chicago. At first the massing of Inter-War Stripped Classical was employed, later followed by the more flowing lines of Art Deco. Local architects were not slow to accept the new challenges required in the construction of taller, more massive buildings. The firm of Atkins and Mitchell was responsible for the DIC Building (now Harbour City Centre) in 1928 whereas JM Dawson had planned the Hope Gibbons Building, a rather more traditional structure, in Dixon Street in 1925. He was also responsible for Wakefield Chambers on the corner of Wakefield Street and Taranaki Street in 1928. The huge new commercial buildings of the 1920s took advantage of the increasing availability and affordability of electric power for lighting, heating, lifts and the pumping of water. Telephones could be fitted in every office; central heating started to be installed, and there was better fire-fighting equipment. Steel-framed buildings were less susceptible to earthquake shocks. Many of the buildings we describe here are still standing, although often modified for other uses. They have become iconic structures reflecting the marked advances of the 1920s era.